Análisis del impacto del COVID 19 en el comportamiento de las barreras de compra en el comercio electrónico de los supermercados en los hogares de la ciudad de Lima - Chang Kuoman, Josue Guillermo Cesar (2022)
This research proposes to demonstrate the reduction of purchase barriers in household electronic commerce in the city of Lima, specifically in the purchase of household products in supermarkets, due to the restrictions imposed by the Peruvian government to counter the pandemic of covid-19. The research makes use of a mixed method with surveys of 385 households in the city of Lima and an interview with experts in electronic commerce. The research shows that a% of households saw their online purchases increased, and that they overcame the barriers they had, and that 50% of those surveyed expect to maintain the same frequency of online shopping after the COVID-19 crisis.